Identity Negotiation as Social Adaptation: Third Space Formation among Ethnic Chinese Students in Multicultural Indonesian Universities - Nawaf, Azmi; Sahrul; Rubino (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the social adaptation of Ethnic Chinese students in multicultural public universities in Medan, Indonesia, and explain how the Third Space emerges through identity negotiation within campus environments influenced by Islamic social norms. This study employed a qualitative approach within a constructivist paradigm. The research was conducted at Universitas Sumatera Utara (USU) and Universitas Negeri Medan (UNIMED), involving ten Ethnic Chinese undergraduate students selected through purposive sampling. Data were collected through semi-structured in-depth interviews and supporting documentation and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that social adaptation did not occur through complete cultural assimilation but through ongoing identity negotiation, enabling participants to maintain their cultural values while developing harmonious relationships with students from different ethnic and religious backgrounds. Islamic social norms were perceived as shared social values that encouraged mutual respect and inclusive interaction rather than cultural domination. The study concludes that the Third Space emerged through everyday intercultural interactions, allowing Ethnic Chinese identity and Islamic social norms to coexist within an inclusive social environment. These findings extend Bhabha's Third Space framework in explaining minority students' social adaptation in multicultural higher education settings.